Factors Affecting the Assertive Communication Skills of Young Women at the Jayapura Mercy Princess Orphanage - Paulus Satyo Istandar Tan; Angela Marciana Ayu Saptarina Maturbongs (PT Publikasiku Academic Solution, 2024)
This study aims to determine the factors that influence assertive communication skills in adolescent girls at 'Panti Asuhan Putri Kerahiman Jayapura'. The concept used is assertive communication. The research method used a qualitative approach with in-depth interviews with six informants. The results showed that internal factors include fear, lack of confidence, lack of self-awareness, and emotional situations. External factors include family rules, parenting, social support at the orphanage, and a less supportive environment. The main finding is that adolescent girls in orphanages still have psychological barriers to self-expression and assertiveness. In conclusion, there are internal and external factors that affect the assertive communication skills of adolescent girls in orphanages. Recommendations include the need to provide communication education and training, increase self-awareness, and optimize social support and a conducive environment in orphanages.